Zagreb Indices of the Thorn Jaco Graph (Journal of Informatics and Mathematical Sciences, 2016)
The first three Zagreb indices of a graph \(G\) denoted, \(M_1(G)\), \(M_2(G)\) and \(M_3(G)\), are well known.\ In this paper we derive recursive formula for these indices for the family of thorn Jaco graphs. The concept of a vertex invaded graphis also introduced.
Keywords: Jaco graph; Thorn Jaco graph; Zagreb indices; Vertex invaded graph